SWOT analysis of potato cultivation under arid conditions in western Rajasthan (India) - RANA, RAJESH K; ARYA, SUSHMA; KUMAR, SANJAY; SINGH, DHIRAJ K; CECILIA, T; MARES, V; QUIROZ, R; KADIAN, M S (The Indian Journal of Agricultural Sciences, 2017)
India aims to produce 125 million tonnes potatoes in 2050 for ensuring food security to its natives and for achieving this massive target the country needs to explore non-traditional areas. Rajasthan in general and Jodhpur district in particular are dominated by the arid climate. The state in general and the study area in particular are not known for potato cultivation. CIP-SWCA, New Delhi and ICAR-CPRI, Shimla jointly identified potential location in Jodhpur district for successful potato introduction. SWOT analysis of socio-economic and agro-climatic factors for potato cultivation in this area is based on 110 farmers’ responses. The paper identified a large number of strengths and opportunities linked to potato cultivation in the area while the recognised weaknesses and threats can be mitigated with the use of technology and through the process of focussed rural development. Agriculture in the study area, needs enhanced impetus of agricultural extension machinery and special hand-holding of relatively less aware farmers by the project implementing agency, for bringing in the desirable change.